Water Security and Governance in Catchments - Pacheco, Fernando A.L; Sanches Fernandes, Luís Filipe (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This book addresses several issues on water security and governance, helping readers to understand how the desire for water-secure basins can be accomplished through an interplay of water security, water resources management and water policies. The book contains a collection of 12 papers addressing specific as well as interlinked topics within the Special Issue scope. The editors are grateful to all contributors who made the book a reality.